Effects of Increasing Feed Rate on Tool Deterioration and Cutting Force during End Milling of 718Plus Superalloy Using Cemented Tungsten Carbide Tool - Nurul Hidayah, Razak; Zhan, W. Chen; Timotius, Pasang (MDPI AG, 2017)
Understanding how feed rate (ft) affects tool deterioration during milling of Ni-based superalloys is practically important, but this understanding is currently insufficient. In the present study using a 718Plus Ni-based alloy and cemented tungsten carbide tool inserts, milling experiments were conducted with ft = 0.10 mm/tooth under either dry or wet (with coolant) conditions. The results are compared to those based on using ft = 0.05 mm/tooth from previous studies. The milling force (F) was monitored, the cutting tool edge was examined and the flank wear (VBmax) was measured. As would be expected, an increase in ft increased F. It was found that F correlated well with VBmax for the high ft (0.1 mm/tooth) experiments, as opposed to the previously observed poor F-VBmax relationship for the lower ft (0.05 mm/tooth) value. This is explained, supported by detailed failure analysis of the cutting tool edges, by the deterioration mode to be dominantly edge chipping with a low occurrence of fracturing along the flank face when the high ft was used. This dominancy of the deterioration mode means that the tool edge and workpiece contact was consistent and thus resulted in a clear F-VBmax relationship. A clear F-VBmax relationship should then mean monitoring VBmax through monitoring F is possible.